Effects of postharvest ultraviolet-C treatment on shelf-life and quality of bitter gourd fruit during storage. (June 2021) - Prajapati, Uma; Asrey, Ram; Varghese, Eldho; Singh, A.K.; Pal Singh, Madan
Graphical abstract: Highlights: UV-C treatment has increased storage life of bitter gourd fruits up to 16 days under cold condition in a dose dependent way. UV-C 40 min treatments was found best in retention of quality attributes except ascorbic acid during storage. UV-C treatments with increase in exposure time, increases defence related compounds during storage. Abstract: The aim of this experiment was to study the effect of varied UV-C exposure time (20, 30, 40 minutes) on nutraceutical properties, defence-related compounds, and storage life of bitter gourd fruit. Treated fruit was stored in a cold room maintained at 10 °C temperature and 85–95 % relative humidity for 16 days. UV-C treatment for 40 min was found better in improving antioxidant activity by inhibiting DPPH to 57 %, increasing total phenols to 61 %, total carotenoid to 134 % and total chlorophyll to 61.9 % during 16 days of storage period in comparison with control. UV-C treatment for 40 min was unable to maintain ascorbic acid and reduced its level to 15 % as compared to control on 16 th day of storage. UV-C 40 min treatment has also shown positive effects in maintaining fruit firmness, reducing weight loss and fruit decay percent. Longer exposure to UV-C seems to enhance the abiotic stress level in bitter gourd fruit and it leads to the formation of defence-related compounds like MDA and proline. These compounds conjoin stored fruit in alleviating stress and maintaining a higher concentration of secondary metabolites. This suggests that the application of UV-C for 40 min can be gainfully utilized for enhancing shelf-life and retaining desirable quality parameters during storage of bitter gourd fruit.